Empirics of International Currencies: Network Externalities, History and Persistence - Flandreau, Marc; Jobst, Clemens (The Economic journal (London), 2009)
Using a new database for the late nineteenth century, when the pound sterling was the world's leading international currency, this article provides evidence on the empirical determinants of international currency status. We report evidence in favour of the search-theoretic models to international currencies. Using a microeconomic model of currency choice, we provide empirical support to strategic externalities. We find strong confirmation of the existence of persistence, but reject the view that the international monetary system was subject to pure path dependency and lock-in effects, suggesting that, even in the absence of WWI, the USD was bound to overtake sterling.